Comparison of Community Responses to Clean Water Facilities The KOTAKU Program in Bekasi Regency - Rabbani, Muhammad Gibran; Marsoyo, Agam (Universitas Ibn Khaldun Bogor, 2023)
Efforts to successfully build a slum management program are related to spatial and non-spatial characteristics. The government helped address slums through the KOTAKU program. One of its activities is clean water facilities that involve community participation. Differences in characteristics in the city center and suburbs resulted in diverse implementations and community responses. This study aims to compare the community's response to the clean water facilities of the KOTAKU Program in Pasirsari and Mekarsari Villages, Bekasi Regency, as an evaluation of the KOTAKU program implemented by the government. The research method uses quantitative and descriptive qualitative methods, with a sample of 120 people. The results showed that the community response to the efficiency variable showed that the majority of the responses agreed, and there was no difference, as well as the responses to the effectiveness and sustainability criteria. The effectiveness variable suggests that most reactions agree, and there is no difference. The sustainability variable show that most responses agree, and there is no difference. The study concludes that the majority of the community's response to the clean water facilities of the KOTAKU program is no different, meaning that the program has the same reaction with good efficiency, effectiveness, and sustainability in city center and suburbs.